Nodal Langerhans cell neoplasm: detailing the diagnostic quandaries - Zachariah Chowdhury; Juhi Varshney; Anil Singh; Satvik Khaddar (University of São Paulo, 2022)
Langerhans cells, found in the supra-basal region of the mucous membranes in the epidermis of the skin, in lymph nodes and thymus, function as antigen-presenting cells within the histiocyte system. Tumors derived from Langerhans cells (LC) can be divided according to the degree of cytological atypia and clinical behavior into Langerhans cell histiocytosis (LCH) and Langerhans cell sarcoma (LCS). LCS is rare, and the nodal presentation is even rarer with challenging histological characteristics. LCS has a dismal overcome despite intensive chemotherapy. Herein, we report a case of a 29-year-old male who presented with generalized lymphadenopathy initially considered as a lymphoma. An outright definitive diagnosis could not be attained in the initial histomorphological and immunohistochemical evaluation, fraught with differential diagnoses. The key to decoding the precise neoplasm was a combination of the cytopathologic features, review of the histomorphology, and extensive immunohistochemical assessment in conjunction with the clinical and positron emission tomography (PET) scan findings. The best diagnosis proffered was a Langerhans cell histiocytosis progressing to Langerhans cell sarcoma. This case highlights the grey zone areas in LC neoplasms, the diagnostic conundrums encountered, the indispensable role of meticulous pathological analysis, and the importance of ancillary studies in hammering out the final diagnosis.